2017
DOI: 10.1016/j.amsu.2017.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications post ultrasound guided renal biopsy - A single centre experience from Pakistan

Abstract: IntroductionRenal biopsy is the diagnostic modality of choice for the diagnosis of renal parenchymal diseases. The advent of improved imaging techniques and biopsy needles over the years has increased the safety of the procedure and the ability to obtain adequate renal tissue for diagnosis. However, there is paucity of data in this regard from Pakistan. This study shall help in establishing the local perspective of the frequency of bleeding complications in percutaneous ultrasound guided renal biopsy.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…Similar results were published by the Norwegian registry on 8573 biopsies [6]. Still, there were studies which did not confirm this association [8], [9] emphasising the history of hypertension as a factor and not the present blood pressure. In our study group, the vast majority of patients had a history of hypertension (74%), but only current hypertension increased the bleeding risk as an independent predictor.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were published by the Norwegian registry on 8573 biopsies [6]. Still, there were studies which did not confirm this association [8], [9] emphasising the history of hypertension as a factor and not the present blood pressure. In our study group, the vast majority of patients had a history of hypertension (74%), but only current hypertension increased the bleeding risk as an independent predictor.…”
Section: Discussionsupporting
confidence: 78%
“…In the assessment of the factors associated with biopsy complications, our results confirmed the previously recognised traditional bleeding factors. Higher serum creatinine and AKI were significant confounding factors in biopsy complications in a large multicentric study on 2563 patients [16] but were also found in smaller monocentric studies, as ours [8], [11]. In our results, these factors lost statistical significance in the multivariate model.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, it is possible that complications with less pronounced clinical or biochemical features were not identified. In a study conducted by Azmat et al (22) , involving 220 patients, complications occurred in 42 patients (19.1%), major complications, including hypotension and a significant hematoma requiring blood transfusion, occurring in 16 patients (7.3%) and minor complications, including macroscopic hematuria and renal hematoma < 5 cm, occurring in 26 (11.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Major complications of transplant biopsies are variously described in the literature but predominantly comprise haemorrhage requiring transfusion, radiological intra-arterial embolization or surgical intervention. Recent studies of native kidney biopsies have described the risk of such bleeding complications as 2.2 to 7.4% [ [4] , [5] , [6] ]. Fewer data exist for transplant biopsies.…”
Section: Introductionmentioning
confidence: 99%